2020
DOI: 10.1159/000507196
|View full text |Cite
|
Sign up to set email alerts
|

Major Predictive Factors for Progression of Early to Late Age-Related Macular Degeneration

Abstract: Introduction: We present a prediction model for progression from early/intermediate to advanced age-related macular degeneration (AMD) within 5.9 years. Objectives: To evaluate the combined role of genetic, nongenetic, and phenotypic risk factors for conversion from early to late AMD over ≥5 years. Methods: Baseline phenotypic characteristics were evaluated based on color fundus photography, spectral-domain optical coherence tomography, and infrared images. Genotyping for 36 single-nucleotide polymorphisms as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 52 publications
(76 reference statements)
0
12
0
Order By: Relevance
“…RPE-damaged cells release cytokines and chemokines that recruit and activate choroid dendritic cells, which amplify the inflammatory process due to cell-cell contact, overall triggering a chronic inflammation that has been reported to play a key role in the AMD pathogenicity [81]. Indeed, genetic risk variants may exacerbate the inflammatory response due to OS in the retina, and several polymorphic variants in genes encoding or regulating key complement proteins have been associated to AMD [82]. The major genetic risk factor to develop AMD is the Y402H polymorphism of complement factor H (CFH), which reduces CFH's ability to neutralize the effect of oxidized photoreceptor phospholipids from photoreceptors, which are incorporated into the RPE membrane and trigger RPE cell apoptosis [83,84].…”
Section: Oxidative Stress and Age-related Macular Degeneration (Amd)mentioning
confidence: 99%
“…RPE-damaged cells release cytokines and chemokines that recruit and activate choroid dendritic cells, which amplify the inflammatory process due to cell-cell contact, overall triggering a chronic inflammation that has been reported to play a key role in the AMD pathogenicity [81]. Indeed, genetic risk variants may exacerbate the inflammatory response due to OS in the retina, and several polymorphic variants in genes encoding or regulating key complement proteins have been associated to AMD [82]. The major genetic risk factor to develop AMD is the Y402H polymorphism of complement factor H (CFH), which reduces CFH's ability to neutralize the effect of oxidized photoreceptor phospholipids from photoreceptors, which are incorporated into the RPE membrane and trigger RPE cell apoptosis [83,84].…”
Section: Oxidative Stress and Age-related Macular Degeneration (Amd)mentioning
confidence: 99%
“…Interestingly, in this study, RPD showed only slight correlation with CFB and none of the other complement factors. Like DV and HRF, RPD have been also recognized as a risk factor for progression to advanced AMD [23,24,47,48].…”
Section: Discussionmentioning
confidence: 99%
“…The findings also correspond to genetic studies, which showed an association between greater DV and drusen area with higher number of AMD risk alleles in complement genes [ 34 36 ]. Several clinical studies suggested using DV as a quantitative tool to assess the risk for AMD progression [ 23 , 37 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations